ANALISIS JUMLAH KEBUTUHAN DOKTER UMUM DI UPT PUSKESMAS PISANGAN DENGAN METODE WORKLOAD INDICATORS OF STAFFING NEED (WISN) TAHUN 2022 - Tasya Meilani Putri (2022)
The human resources in health institutions determine one aspect of the quality of service, so proper planning and fulfillment of human resource needs is required. One method of planning human resource needs in health institutions is the Workload Indicators of Staffing Need (WISN) method. This research is a type of descriptive qualitative research with observations using work sampling techniques, document review, and interviews, which aims to determine the number of general doctors needed at the General Poly Pisangan Health Center. Work sampling was conducted for ten minutes on six working days. The total working time available for general doctors at Pisangan Health Center in a year was 76.658 minutes, according to the findings. The standard workload for main activities is 17.562 general medical services; 8.471 follow-up services; 19.366 referral services; and 19.916 medical certificate services. The standard unit of allowance is 1,01 minutes. The results of the study using the WISN method found that there was a shortage of general practitioners at Pisangan Health Center of as many as 1 person from the current number, namely 2. It is hoped that there will be additional general doctors and evaluations to improve service quality standards.